IMPLEMENTASI MODEL PEMBELAJARAN BLANDED LEARNING MELALUI APLIKASI TELEGRAM UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMK SAMUDRA NUSANTARA MAKASSAR - Nurul Iman, Nurazizah, Nurfaida Tasni (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
This study aims to improve students' mathematics learning outcomes in Class XII Computer Engineering Department of SMK Samudra Nusantara Makassar through the application of the Blended Learning learning model using the telegram application in mathematics lessons with Enumeration Rules Material. This type of research is action research conducted at Samudra Nusantara Vocational School, to be precise, class XII of the Department of Computer Engineering in the odd semester of 2022/2023, with a total of 14 people. Data collection was carried out using tests of students' mathematics learning outcomes and observations at each meeting. The data obtained were then analyzed using quantitative and qualitative analysis. The score in cycle I obtained the average value of student learning outcomes of 69.07 and the variance of 177.61 and the standard deviation of 113.33 with an ideal score of 100. In cycle II, learning outcomes were obtained students with an average score of 87 student learning outcomes and a variance of 44.33 and a standard deviation of 6.66 with an ideal score of 100.